Predictors of Procurement Selection: An Investigation of Traditional and Integrated Methods in Nigeria - Martin Oloruntobi Dada (Journal of Construction in Developing Countries, 2012)
A nation's construction industry plays a pivotal role in the nation's development. While the arrangement and organisation of participants for construction procurement is critical to project delivery, participants are often faced with a maze of possible procurement paths. This study used 94 construction projects in Nigeria that were executed or being executed with the traditional or integrated project procurement methods. A logistic regression analysis was conducted using dependent and independent variables. A model for predicting the chosen procurement method evolved from this analysis. The developed model was significant, and its robustness was validated. The model's predictive use is recommended for projects in the research environment. Further examination of ethical and cultural issues with respect to construction procurement in the research environment is recommended. Furthermore, a similar study should be done in countries with similar or dissimilar characteristics to elicit the effects of geographical and cultural differences.